Intravitreous delivery of melatonin affects the retinal neuron survival and visual signal transmission: in vivo and ex vivo study. (1st January 2020) - Tao, Ye; Hu, Bang; Ma, Zhao; Li, Haijun; Du, Enming; Wang, Gang; Xing, Biao; Ma, Jie; Song, Zongming
Abstract: Intravitreal delivery can maximize the intensity of therapeutic agents and extend their residence time within ocular tissue. Melatonin is a lipophilic molecule that crosses freely biological barriers and cell membranes. This study intends to investigate the effects of intravitreally delivered melatonin on mouse retina. The visual function of administered mice is assessed by electrophysiological and behavior examinations three weeks after intravitreal delivery. Moreover, multi-electrode array (MEA) was used to assess the electrical activities of retinal ganglion cells (RGCs). We found that intravitreal delivery of high dosage melatonin (400–500 µg/kg) destroyed the retinal architecture and impaired the visual function of mice. Conversely, the melatonin administration at low dose (100–300 µg/kg) did not have any significant effects on the photoreceptor survival or visual function. As shown in the MEA recording, the photoreceptors activity of the central region was more severely disturbed by the high dose melatonin. A pronounced augment of the spontaneous firing frequency was recorded in these mice received high dosage melatonin, indicating that intravitreal delivery of high dosage melatonin would affect the electrical activity of RGCs. Immunostaining assay showed that the vitality of cone photoreceptor was impaired by high dose melatonin. These findings suggest that intravitreal melatonin is not always beneficial for ocular tissues, especially when it is administered at high dosage. These data add new perspectives to current knowledge about melatonin delivery at the ocular level. Further therapeutic strategies should take into consideration of these risks that caused by delivery approach.